Emotional Engagement in Undergraduate Thesis Writing: Systematic Review - Moesarofah Moesarofah; Endah Yulia Rahayu (Universitas PGRI Adi Buana Surabaya, 2023)
This systematic review of the last seven years aims to identify and analyze emotional engagement in academic writing or undergraduate thesis. Referring to Pekrun's academic, emotional theory, the object focus in writing a thesis is loaded with emotional content besides cognitive and social aspects. The discrepancy between the error and the targeted plan evokes positive and negative emotions. Ten relevant studies in the literature search between 2016-2022 are included in the review, indicating that the research theme requires the attention of researchers to develop further studies. The results of the review show that anxiety is the dominant emotion students feel when writing their undergraduate thesis in various countries. The review results are grouped into theoretical basis, research methods, and relevant results. Implications for future research indicate that self-regulation and strengthening the social environment bring positive consequences in writing an undergraduate thesis. Meanwhile, the study’s limitations are related to the inclusion criteria that are too restrictive.